Characterization of a transmission positron/positronium converter for antihydrogen production - Aghion, Stefano; Demetrio, Andrea; Müller, Simon R.; Oberthaler, Markus K.; Zimmer, Christoph (Nuclear instruments & methods in physics research. Section B, Beam interactions with materials and atoms, 2017)
In this work a characterization study of forward emission from a thin, meso-structured silica positron/positronium (Ps) converter following implantation of positrons in light of possible antihydrogen production is presented. The target consisted of a ∼1μm thick ultraporous silica film e-gun evaporated onto a 20nm carbon foil. The Ps formation and emission was studied via Single Shot Positron Annihilation Lifetime Spectroscopy measurements after implantation of pulses with 3-4·107 positrons and 10ns temporal width. The forward emission of implanted positrons and secondary electrons was investigated with a micro-channel plate - phosphor screen assembly, connected either to a CCD camera for imaging of the impinging particles, or to a fast photomultiplier tube to extract information about their time of flight. The maximum Ps formation fraction was estimated to be ∼10%. At least 10% of the positrons implanted with an energy of 3.3keV are forward-emitted with a scattering angle smaller than 50° and maximum kinetic energy of 1.2keV. At least 0.1-0.2 secondary electrons per implanted positron were also found to be forward-emitted with a kinetic energy of a few eV. The possible application of this kind of positron/positronium converter for antihydrogen production is discussed.
Gesehen am 14.12.2018